Electrical appliances protection using auto cut under voltage and over voltage tripping mechanism - Abu Bakar, Nur Hijrah; Mohd Asry, Anis Maisarah; Mustafa -, Farahiyah (FAZ Publishing, 2020)
Power quality is a term that refers to maintaining the near sinusoidal waveform of power distribution bus voltages and current at rated magnitude and frequency. The most common types of power quality problem are voltage sag, harmonic distortion, voltage spike, noise, under voltage and over voltage. The development of a low voltage and high voltage tripping mechanism where studied to protect the load from damage due to under voltage and over voltage problem. In this study, an auto-cut circuit has been designed using relay, transistor, operational amplifier and other discrete component and a lamp was used as a load to confirm the circuit successfully operated. The results show that when the supply in under voltage condition, the load will turn OFF when the supply voltage below 210 V. When the supply voltage rises above 240 V the load will turn OFF and it show overvoltage condition. The advantage of this protection circuit is to protect load from the fluctuation of voltage that can cause damage to load. The GSM modem can be used as a path to send message/alert to user via SMS in future.